2023
DOI: 10.3390/met13081419
|View full text |Cite
|
Sign up to set email alerts
|

Statistically Modeling the Fatigue Life of Copper and Aluminum Wires Using Archival Data

Abstract: It has been known for at least 150 years that fatigue life data exhibits a considerable amount of variability. Furthermore, statistically modeling fatigue life adequately is challenging. Different empirical approaches have been used, each of which has merit; however, none is appropriate universally. Even when a sufficiently robust database exists, the scatter in the fatigue lives may be extremely large and difficult to characterize. The purpose of this work is to review traditional and more modern empirically … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…However, serve as a reference for understanding how the different factors affect fatigue. A study elucidating statistical models of copper fatigue can be found in Harlow [64], although its scope is confined to annealed electrolytic copper wire tested in reverse torsion fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…However, serve as a reference for understanding how the different factors affect fatigue. A study elucidating statistical models of copper fatigue can be found in Harlow [64], although its scope is confined to annealed electrolytic copper wire tested in reverse torsion fatigue.…”
Section: Discussionmentioning
confidence: 99%